Quantitative Characterization of the Exposure–Response Relationship for Cancer Immunotherapy: A Case Study of Nivolumab in Patients With Advanced Melanoma. (26th December 2016) - Wang, X; Feng, Y; Bajaj, G; Gupta, M; Agrawal, S; Yang, A; Park, J‐S; Lestini, B; Roy, A
Abstract : To inform the benefit–risk assessment of nivolumab in patients with advanced melanoma, analyses of efficacy and safety exposure–response (E–R) relationships were conducted with data from patients with advanced melanoma enrolled in two clinical studies (phase I and phase III) who received nivolumab 0.1–10.0 mg/kg every 2 weeks. E‐R efficacy analyses were performed by relating the nivolumab time‐averaged concentration after the first dose (Cavg1 ) to two endpoints: RECIST objective response (OR) and overall survival (OS). E–R safety analyses characterized the relationship between nivolumab Cavg1 and the hazard of all‐causality adverse events leading to discontinuation or death (AE‐DC/D). Nivolumab exposure represented by Cavg1 was not a significant predictor of OR, OS, or the hazard of AE‐DC/D. E–R efficacy and safety relationships were relatively flat over the exposure range.